2020
DOI: 10.1002/cti2.1180
|View full text |Cite
|
Sign up to set email alerts
|

Is glaucoma an autoimmune disease?

Abstract: There is increasing evidence from animal and human studies that glaucoma is an autoimmune disease. Evidence for this hypothesis includes the fact that antibodies as well as T‐cell responses to heat‐shock proteins (HSPs) are detectable in some patients with glaucoma and in an animal model of the disease. As in the human disease, experimental animal models of glaucoma have been found to demonstrate neurodegenerative changes in the optic nerve associated with immunoglobulin and T‐cell infiltration. Although there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…They showed that glaucomatous eyes had a reduced blood flow and vessel density in the optic nerve head compared to control eyes. Additionally, Wang, et al, [38] showed that OCTA measurements correlate with visual field measurements, indicating that OCTA provides a direct route to assessing retinal perfusion. Thus, measurement of RVP and use of OCTA look to be valuable tools in assessing retinal health in glaucoma.…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…They showed that glaucomatous eyes had a reduced blood flow and vessel density in the optic nerve head compared to control eyes. Additionally, Wang, et al, [38] showed that OCTA measurements correlate with visual field measurements, indicating that OCTA provides a direct route to assessing retinal perfusion. Thus, measurement of RVP and use of OCTA look to be valuable tools in assessing retinal health in glaucoma.…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…Development of Open-Angle Glaucoma in Adults With Seropositive Rheumatoid Arthritis in Korea Glaucoma exhibits a pathogenic pathway involving RGC loss, optic nerve damage, and corresponding visual field defects, but the underlying mechanisms of glaucomatous neuronal damage are not clear. 47 Evidence that glaucoma is an autoimmune disease is steadily growing, 48 including the discovery of an IgG autoantibody in human glaucomatous retina, and autoantibodies and T-cell responses to HSP detected in some patients with glaucoma. [49][50][51] Increased serum autoantibodies against HSP27 observed in patients with glaucoma and IOP-independent RGC loss in animal models after immunization with HSP27 also provide evidence that the immune system is involved in the pathogenesis of glaucoma.…”
Section: Jama Network Open | Rheumatologymentioning
confidence: 99%
“…Большое количество данных [9][10][11], полученных в результате клинических и экспериментальных исследований, убедительно свидетельствуют об участии иммунной системы в развитии глаукомы. При этом описываются одновременно как нейропротективная, так и нейродеструктивная роль иммунной системы.…”
Section: оригинальные статьи обсуждениеunclassified